Pemodelan 3D pada Bangunan Gedung Guna Mendukung Implementasi Bim 5D pada Proyek Konstruksi - Yudiayanto, Rakha Radhitya Putra; Winanda, Lila Ayu Ratna; Sunarwadi, Hadi Surya Wibawanto; Kartika, Deviany (Universitas Batanghari Jambi, 2025)
Nowadays, many have developed in terms of technology and many other sectors. The use of The use of the latest technology also has a big impact on the construction business in Indonesia. Indonesia. Technological developments in the construction sector also have an impact on increasing the value of development efficiency. BIM can overcome work delays and minimize errors in calculating costs on some construction work Therefore, the purpose of this research is to modeling the structural system in three dimensions (3D) on the building as part of the Building Information Modeling (BIM) implementation. The method used in this research is by modeling working drawings and materials previously obtained from working drawings and materials previously obtained from the project used as the object of research into a three-dimensional (3D) object. object of research into a three-dimensional (3D) object using relevant and appropriate software, which will support the implementation of the project to support BIM Implementation. implementation of the project to support the Implementation of 5D BIM on construction projects. Construction project. The results showed that the three-dimensional (3D) structural system can be modeled (3D) structural system can be modeled on the work of columns, beams, foundations, stairs, ramp, and floor plate. The results of this research are expected to support implementation of BIM at least up to 5D level so that it can be known the cost efficiency of thecost efficiency in building work